Quality control on the basis of entropy determination - Dissanayake, Yasaratne B.; Pankov, Aleksandr; Shestakov, Vladimir S. (Transport, 2004)
Statistical methods are extensively used in quality control. The method of the application of entropy conception for quality control is proposed. It is based on the use of statistical information about deviations in the operation of a complex system. In the context of this: the structure of the complex system control is considered; the conceptions of controllable and observable systems are introduced. The classification of adverse factor is given influencing upon the system. The example is presented, showing how the application of the proposed method permits to give the evaluation of sources of risks and quality reduction in the complex system.First Published Online: 27 Oct 2010